Swift Prosodic Modulation of Lexical Access: Brain Potentials From Three North Germanic Language Varieties. - Hjortdal, Anna; Frid, Johan; Novén, Mikael; Rolla, Mikael (Journal of Speech, Language & Hearing Research, 2024)
Purpose: According to most models of spoken word recognition, listeners probabilistically activate a set of lexical candidates, which is incrementally updated as the speech signal unfolds. Speech carries segmental (speech sound) as well as suprasegmental (prosodic) information. The role of the latter in spoken word recognition is less clear. We investigated how suprasegments (tone and voice quality) in three North Germanic language varieties affected lexical access by scrutinizing temporally fine-grained neurophysiological effects of lexical uncertainty and information gain. Method: Three event-related potential (ERP) studies were reanalyzed. In all varieties investigated, suprasegments are associated with specific word endings. Swedish has two lexical “word accents” realized as pitch falls with different timings across dialects. In Danish, the distinction is in voice quality. We combined pronunciation lexica and frequency lists to calculate estimates of lexical uncertainty about an unfolding word and information gain upon hearing a suprasegmental cue and the segment upon which it manifests. We used single-trial mixed-effects regression models run every 4 ms. Results: Only lexical uncertainty showed solid results: a frontal effect at 150-400 ms after suprasegmental cue onset and a later posterior effect after 200 ms. While a model including only segmental information mostly performed better, it was outperformed by the suprasegmental model at 200-330 ms at frontal sites. Conclusions: The study points to suprasegmental cues contributing to lexical access over and beyond segments after around 200 ms in the North Germanic varieties investigated. Furthermore, the findings indicate that a previously reported “pre-activation negativity” predominantly reflects forward-looking processing.